2023
DOI: 10.1002/smll.202302347
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal Catalytic Nanozymes Microneedle Patches with Opposite Properties for Wound Management

Abstract: Reactive oxygen species (ROS)‐mediated biological catalysis involves serial programmed enzymatic reactions and plays an important part against infectious diseases; while the spatiotemporal control of catalytic treatment to break the limitations of the disease microenvironment is challenging. Here, a novel spatiotemporal catalytic microneedles patch (CMSP‐MNs) integrated with dual‐effective Cu2MoS4 (CMS) and polydopamine (PDA) nanoparticles (NPs) for breaking microenvironment restrictions to treat wound infecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…Microneedles are needle‐like devices showing advantages in bio‐safety, high mechanical strength, encapsulation possibilities, and many others. [ 12–16 ] Among them, HA microneedles benefit tissue regeneration and drug delivery. [ 17–19 ] In contrast, the GNCs have showed their emerging attracts in biomedical fields, especially the antibiosis studies, due to their multi‐characteristics including bacteriostatic enzyme‐mimic catalytic property, ease of synthesis, size tunability, and good biocompatibility.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Microneedles are needle‐like devices showing advantages in bio‐safety, high mechanical strength, encapsulation possibilities, and many others. [ 12–16 ] Among them, HA microneedles benefit tissue regeneration and drug delivery. [ 17–19 ] In contrast, the GNCs have showed their emerging attracts in biomedical fields, especially the antibiosis studies, due to their multi‐characteristics including bacteriostatic enzyme‐mimic catalytic property, ease of synthesis, size tunability, and good biocompatibility.…”
Section: Introductionmentioning
confidence: 99%
“…[ 20–25 ] Besides, the unique photoluminescence feature of GNCs enables them to emit bright fluorescence under ultraviolet (UV) light, intriguing GNCs for rapid drug dose monitoring. [ 26–28 ] Although many reports have demonstrated the infected wound healing performances of microneedles or GNC‐based nanomedicine, [ 13,29–32 ] the integration of them remained unexplored. Thus, it is conceived that the encapsulation of antimicrobial GNCs into the microneedles would realize effective drug release and residual dose monitoring in the infected wound healing.…”
Section: Introductionmentioning
confidence: 99%
“…These materials can be principally divided into two categories . One category comprises nanozymes with ROS-generating abilities, exhibiting glucose oxidase (GOD)-like or peroxidase (POD)-like activities, commonly employed in treating infected wounds. , The other includes nanozymes with ROS-scavenging capabilities, displaying catalase (CAT)-like or superoxide dismutase (SOD)-like activities, frequently used to mitigate inflammation and enhance the repair of various acute and chronic wounds . Among these, some nanozymes even showcase pH-adjustable enzymatic activity. , In acidic environments, these nanozymes exhibit a predisposition toward peroxidase (POD) or oxidase (OXD) enzymatic activities, whereas under alkaline conditions, they tend to manifest superoxide dismutase (SOD) or catalase (CAT) enzymatic activities. , Numerous studies have suggested that this distinctive property equips these nanozymes with the capacity to exert therapeutic effects in various contexts.…”
Section: Introductionmentioning
confidence: 99%